PEDAGOGICAL CHARACTERISTICS OF EDUCATION OF PHYSICAL SKILLS OF YOUNG FOOTBALL PLAYERS - Jahbarov Abulfayz, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article training young players' physical abilities, the level of strength, quickness, etc., depends only on the development of the tissues, cells, etc. of the body's bones, muscles, and other organs, and information on their proper development is provided.